Marketing of Hollywood Films (Dubbed and Original) in India:A Case on Planning and Executing Marketing Strategy - Prageetha Raju, G. (Indian Journal of Marketing, 2011)
The broad objective is to plan, and implement the various promotional strategies for Hollywood movies, with special reference to the film, "Chronicles of Narnia: Prince Caspian" and "White Horse: The Legend of the Deep" by Sony Pictures Entertainment in Indian Markets. The study specific objectives are to: 1. Assess the effectiveness of the marketing strategies followed by Sony Pictures Entertainment (SPE) films 2. Know the various competitors in the Hollywood movie distribution in Andhra Pradesh and Karnataka. 3. Evaluate the strengths and weaknesses of SPE films 4. Provide suitable suggestions for improvement in the existing as well as future marketing strategies. The study is confined to Andhra and Karnataka region only (Nizam and Mysore territory, to be precise).The study covers the movies Chronicles of Narnia: Prince Caspian and White Horse: The Deep Legend. Data is collected from Primary Data and Secondary Data sources. These movies were released in April-May, 2008. The major limitation of the study is that it is conducted only in two major cities in South India and also the figures and facts regarding ad-pub plans, marketing expenditure and publicity details could not be revealed for public use. The study predominantly comprises of loads of photographs clicked at various multiplexes in order to depict the marketing of the films in the article. The present study is helpful to researchers/academicians interested in the area of film distribution and marketing vis-Ã -vis film distributors (established ones as well as novices) who are foraying into Hollywood film distribution (dubbed and original versions).